ANALISIS KINERJA SUMBER DAYA APARATUR PADA UPTD BALAI PENGAWASAN DAN PENGENDALIAN MUTU BARANG DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI SULAWESI SELATAN - Mustafa Mustafa; Mattalatta Mattalatta; Hasmin Tamsah (AkMen JURNAL ILMIAH, 2015)
This study aims to (1) analyze the performance of personnel resources in the Hall of Goods Quality Supervision and Control of the Department of Industry and Trade of South Sulawesi province. (2) To analyze the factors that support the performance of personnel resources Center for Quality Supervision and Control of Goods Department of Industry and Trade of South Sulawesi province. The research was conducted on Calibration Laboratory, Laboratory Testing and Product Certification in Hall Goods Quality Supervision and Control of the Department of Industry and Trade of South Sulawesi province from November to December of 2014. This type of research is carried out by using the census questionnaire as a data collection tool. The author uses the basic qualitative analysis examines the participants in this case all employees (analysts and functional) in the scope of UPTD Hall Goods Quality Supervision and Control of the strategies that are interactive and flexible. This study aimed to understand social phenomena from the perspective of the participants, this study used to examine the condition of natural objects where the researcher is one of the key instruments of the 32 participants who gave sight. Quantitative analysis is a systematic scientific research on the parts and phenomena and relationships. Quantitative research is to develop and use mathematical models related to phenomena in UPTD Hall Goods Quality Supervision and Control of the Department of Industry and Trade of South Sulawesi province. The central part of the measurement process in this study provides a fundamental relationship between empirical observation and mathematical expression of quantitative relationships. Level of performance of the apparatus UPTD BPPMB Department of Industry and Trade of South Sulawesi province showed relatively Good. It is based on the variable work practices and work, high performance of individual officers condition manifested in the good performance of the organization UPTD BPPMB Department of Industry and Trade of South Sulawesi province as a public service organization.This study aims to (1) analyze the performance of personnel resources in the Hall of Goods Quality Supervision and Control of the Department of Industry and Trade of South Sulawesi province. (2) To analyze the factors that support the performance of personnel resources Center for Quality Supervision and Control of Goods Department of Industry and Trade of South Sulawesi province. The research was conducted on Calibration Laboratory, Laboratory Testing and Product Certification in Hall Goods Quality Supervision and Control of the Department of Industry and Trade of South Sulawesi province from November to December of 2014. This type of research is carried out by using the census questionnaire as a data collection tool. The author uses the basic qualitative analysis examines the participants in this case all employees (analysts and functional) in the scope of UPTD Hall Goods Quality Supervision and Control of the strategies that are interactive and flexible. This study aimed to understand social phenomena from the perspective of the participants, this study used to examine the condition of natural objects where the researcher is one of the key instruments of the 32 participants who gave sight. Quantitative analysis is a systematic scientific research on the parts and phenomena and relationships. Quantitative research is to develop and use mathematical models related to phenomena in UPTD Hall Goods Quality Supervision and Control of the Department of Industry and Trade of South Sulawesi province. The central part of the measurement process in this study provides a fundamental relationship between empirical observation and mathematical expression of quantitative relationships. Level of performance of the apparatus UPTD BPPMB Department of Industry and Trade of South Sulawesi province showed relatively Good. It is based on the variable work practices and work, high performance of individual officers condition manifested in the good performance of the organization UPTD BPPMB Department of Industry and Trade of South Sulawesi province as a public service organization.